"It's my body and my life": A dialogued collaborative autoethnography - Martínez, Alejandra (2015)
In this essay, we reflect on others' perceptions of women who choose not to be mothers, and our own sensations and feelings in relation to people's judgments about our own decision to remain childfree. We use a specific dynamic that we name dialogued collaborative autoethnography to address our personal stories within the social and cultural context.